Higher integrability of iterated operators on differential forms. (November 2016) - Ding, Shusen; Shi, Guannan; Xing, Yuming
Abstract: In this paper, we first prove the local higher integrability and higher order imbedding theorems for the iterated operators defined on differential forms. Then, we prove the global higher integrability and higher order imbedding inequalities for these operators. Finally, we demonstrate applications of the main results by examples.